Value creating activity from aluminium recycling on metal scrap collector site: Malaysia case study - Rakiman, Umol Syamsyul; Raja Mohd Rasi, Raja Zuraidah; Ahmad Latiffi, Aryani; Shahbaz, Muhammad Saeed (IOP Publishing, 2018)
This research is on the value creating activities from aluminium recycling on the metal scrap collector site. Less is known on how value is created from recycling. Value creation is important in order to generate profit. Metal scrap collector is one of the main component in the recycling chain which creates value for recycling. Understanding the value creation part of metal scrap collector will help to understand the value creation from recycling as metal scrap collector is one of the actors in the recycling industry. A case study was conducted in order to gather the data for this research. An indepth interview session was done with Managing Director of the metal scrap collector firm. A few value creating activities were identified consisting of two categories which is primary and supporting activities. Eventhough the separation between primary and supporting activities is in line with the value chain analysis by Porter. But the activities in the primary and supporting section differs slightly in a few section. This indicates that the value creation activities in the metal scrap collector differs from the original value chain analysis by Porter. Further research on other actors in the recycling value chain is needed in order to test the homogenousity throughout the recycling calue chain.